SIN3A Regulates Porcine Early Embryonic Development by Modulating CCNB1 Expression - Luo, Lei; Dang, Yanna; Shi, Yan; Zhao, Panpan; Zhang, Yunhai; Zhang, Kun (Frontiers in Cell and Developmental Biology, 2021)
SIN3A is the central scaffold protein of the SIN3/histone deacetylase (HDAC) transcriptional repressor complex. SIN3A participates in the mouse preimplantation development by fine-tuning HDAC1 expression. However, it remains unresolved if this functional significance of SIN3A was conserved in other mammals. Herein, RNA-seq results show a large amount of SIN3A mRNA is present in oocytes and early embryos prior to embryonic genome activation and a low amount thereafter, suggesting a maternal origin of SIN3A in pigs, cattle, mice, and humans. Interestingly, immunofluorescence data show that SIN3A protein level peaks at four-cell stage in pigs compared with morula stage in cattle. SIN3A depletion in early embryos causes a developmental arrest at two-cell stage in pigs but does not affect bovine early embryonic development. In contrast with mouse data, SIN3A depletion results in only a slight decrease and even no difference in HDAC1 expression in porcine and bovine early embryos, respectively. In addition, HDAC1 knockdown does not cause two-cell block but leads to a reduced blastocyst rate. By using unbiased RNA-seq approach, we found that Cyclin B1 (CCNB1) transcript level is dramatically reduced. Moreover, CCNB1 knockdown results in a similar phenotype as SIN3A depletion. Injection of exogenous CCNB1 mRNA into SIN3A-depleted embryos could partly rescue embryonic development to pass two-cell stage. In conclusion, our results indicate SIN3A plays an essential role in porcine early embryonic development, which probably involves the regulation of CCNB1 expression.